أزمة كوفيد-19 بين محرك وعائق للمقاولاتية - بعوني, ليلى (جامعة الوادي - University of Eloued, 2023)
يهدف هذا البحث لإبراز مدى تأثير أزمة كوفيد-19 على الحياة الاقتصادية والمقاولاتية بمختلف أنواعها ونشاطاتها وخاصة المؤسسات الصغيرة والمتوسطة والمؤسسات الناشئة، ومدى تأثيرها على بعض القطاعات واقتصاديات مختلف الدول. من خلال هذا البحث تبين أن أزمة كوفيد-19، رغم أنها كانت السبب في تعثر العديد من القطاعات وأثرت سلبا على المؤسسات الصغيرة والمتوسطة في جميع أنحاء العالم، كانت محرك ربح لقطاعات أخرى، وخاصة قطاع الصناعة الصيدلانية، وأعطت دفعا قوي للمؤسسات الناشئة وللمؤسسات الناشطة في مجال التكنولوجيا والرقمنة. في الجزائر، عانت المؤسسات الصغيرة والمتوسطة كثيرا من الأزمة، رغم أن هذه الأخيرة كانت سببا في ظهور العديد من المقاولين والمؤسسات الناشئة. This research aims to highlight the extent to which the COVID-19 crisis affects all different types and activities of economic life and entrepreneurship, especially small and medium enterprises (SME) and start-ups, and its impact on the economies of various countries. This research shows that, despite the fact that Covid-19 crisis was the cause of the faltering of many sectors and negatively affected small and medium enterprises around the world, it was a profit engine for other sectors, especially the pharmaceutical industry, and gave a strong boost to enterprises active in technology, digitization and start-up. In Algeria, small and medium enterprises have suffered a lot from the crisis. On the other side, this crisis has caused the emergence of many entrepreneurs and start-ups.
Covid-19 crisis, between barriers and drivers for entrepreneurship
مقال
Keywords: مقاولاتية ; مؤسسات ناشئة ; كوفيد-19 ; تكنولوجيا ورقمنة; entrepreneurship; start-ups; COVID-19;Technology and digitization.